Case Report: Tocilizumab for the Treatment of SARS-CoV-2 Infection in a Patient With Aplastic Anemia - Keiffer, Gina; French, Zachary; Wilde, Lindsay; Filicko-O'Hara, Joanne; Gergis, Usama; Binder, Adam F. (Frontiers in Oncology, 2020)
While cytokine storm develops in a minority of patients with severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection, novel treatment approaches are desperately needed for those in whom it does. Tocilizumab, an interleukin-6 receptor antibody, has been utilized for the treatment of cytokine storm in a number of severe inflammatory conditions, including in patients with severe coronavirus disease 2019 (COVID-19). Here, we present the first published case utilizing this therapy in a patient with underlying immunodeficiency. Our patient with aplastic anemia developed cytokine storm due to COVID-19 manifested by fever, severe hypoxia, pulmonary infiltrates and elevated inflammatory markers. Following treatment with tocilizumab, cytokine storm resolved and the patient was ultimately safely discharged from the hospital.